Development of AKM Type Questions (Asesmen Kompetensi Minimum) Containing Ethnoscience Based on CBT (Computer Based Testing) (Case Study: Creative Industry of Jepara District) - Abidin, Zainal; Haryani, Sri; Susilaningsih, Endang (Universitas Negeri Semarang, 2024)
The challenges of the industrial revolution 4.0 encourage curriculum development to equip students with 21st century skills, such as critical thinking skills, creativity and digital literacy. It was recorded that Indonesia's 2018 PISA ranking in terms of literacy was unsatisfactory. Therefore, the National Examination was replaced with a Minimum Competency Assessment (AKM) so that students' literacy skills are better honed. This research focuses on developing AKM type questions based on CBT (Computer Based Testing) (Case Study: Jepara Regency Creative Industries). It is hoped that from this research, students can think more critically, creatively and innovatively in solving problems. The questions consist of 40 questions with 5 types, namely multiple choice, complex multiple choice, description, short answer, and matching. Tested on 39 class XI students of Muhammadiyah 2 Mayong High School using a random sampling method. Based on the feasibility test of the question instrument, the result was 92.03 with the category very suitable for use. Meanwhile, for the validity test results, the score was 0.316 in the valid category, reliability 1 in the reliable category, difficulty level 0.24 and differential power 0.46 in the good category